Understanding Material Text Cultures. A Multidisciplinary View - Hilgert, Markus (Ed.) (Materiale Textkulturen, 2016)
The present volume comprises 6 highly original studies on material text cultures in different nontypographic societies stretching from the 3rd millennium cuneiform textual record of Ancient Mesopotamia to 20th century Qur'anic boards of northern and central African provenience. The volume provides a multidisciplinary approach to material text cultures complementary to the interdisciplinary, strongly theory-grounded research scheme of the CRC 933.